Islamic Religious Education Learning Strategy Based on Literacy and Exemplary Behavior in Forming Disciplined and Responsible Character of Students at Madrasah Aliyah Manbail Futuh - Ikhda Nilla Rosyida; Sholikah (Konsultan Jurnal Ilmiah Indonesia, 2026)
This study aims to analyze the implementation of literacy-based and exemplary Islamic Education (PAI) learning strategies in shaping students’ discipline and responsibility character at Madrasah Aliyah Manbail Futuh. This research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving Islamic education teachers, homeroom teachers, and students. The results indicate that literacy-based learning enhances students’ understanding of Islamic values critically and reflectively, while teacher exemplification plays a crucial role in instilling discipline, responsibility, and good moral character. The integration of literacy and exemplary strategies creates a conducive learning environment and supports the holistic development of students’ cognitive, affective, and psychomotor aspects. Therefore, literacy-based and exemplary PAI learning strategies are proven effective in shaping disciplined and responsible student character in Madrasah Aliyah.